THE PHILOSOPHY OF SOCIAL SCIENCE IN THE ERA OF CLIMATE CHANGE: TOWARDS A NEW ONTOLOGY OF HUMANNATURE RELATIONS - Anis Shafitri; Abu Khaer (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study focuses on the philosophy of social science in the context of climate change with the aim of exploring the ontological transformation of human-nature relations at the local level. How do communities reconstruct their views of nature from an anthropocentric paradigm towards a more relational ecological consciousness that has implications for everyday social practices? The method used is qualitative with a phenomenological approach, through in-depth interviews, participatory observation, and documentation in Sumberjo Village, Ambulu District, Jember Regency, East Java. Data analysis was conducted thematically using the Miles and Huberman model to interpret community experiences related to climate change. The results of the study show a shift in the community's perspective, which no longer views nature solely as an object of exploitation, but as a partner in sustainable living. This is reflected in adaptive agricultural practices, spiritual interpretations of disasters, and social criticism of the unfair distribution of climate impacts. The implications of this research emphasize the need for social science philosophy to develop a new ontological framework that integrates local experiences, traditional knowledge, and modern epistemology to strengthen ecological justice and sustainable climate adaptation policies.